Very high prevalence of infection with the human T cell leukaemia virus type 1c in remote Australian Aboriginal communities: Results of a large cross-sectional community survey. - Lloyd Einsiedel; Hai Pham; Mohammad Radwanur Talukder; Kerry Taylor; Kim Wilson; John Kaldor; Antoine Gessain; Richard Woodman (Public Library of Science (PLoS), 2021)
Infection with the human T cell leukaemia virus type 1 (HTLV-1) subtype C is endemic among Aboriginal people in central Australia. To provide insights into the risk factors for transmission, we conducted the first large-scale, community-based prevalence study in seven remote Aboriginal communities. Residents >2 years old were invited to participate in the study between August 2014 and June 2018. HTLV-1 infection was defined as a positive western blot (WB) test or a positive HTLV-1 PCR. 720 community residents participated in the study (children <15 years, 142; adults, 578). Prevalences for children and adults were 3.5% (5/142) and 36.8% (213/578), respectively, reaching 49.3% (106/215) for those older than 45 years. A wide range of proviral loads were measured for both asymptomatic and symptomatic participants with no difference within groups according to age or gender; however, median PVL was 1.34 log10 higher for symptomatic participants. The adult prevalence of HTLV-1 infection in central Australia is the highest reported worldwide. Sexual contact is likely to be the predominant mode of transmission.